In vitro and in planta studies on temperature adaptation of exserohilum turcicum isolates from maize in europe and south america - Navarro, Barbara Ludwig; Campos, Raphael de Araújo [UNESP]; de Godoy Gasparoto, Maria Cândida [UNESP]; Tiedemann, Andreas von (MDPI, 2021)
Northern Corn Leaf Blight (NCLB) is a fungal leaf disease in maize caused by Exserohilum turcicum. NCLB occurs worldwide, from tropical to temperate zones raising the question about plasticity of temperature adaptation of local isolates of the pathogen. Seven isolates of E. turcicum originating from South America and seven from Europe were compared for their response to temperature variations in vitro and in vivo between 15 and 30 °C. In vitro, isolates originating from Europe and South America significantly differed in mycelial growth rate at 30 °C and in sporulation at 25 °C and 30 °C. Aggressiveness of E. turcicum isolates was evaluated on three susceptible maize cultivars (maize lines B37, Sus1 and the German hybrid Niklas) under different day/night temperature regimes (15/10 °C, 20/15 °C, 25/20 °C, or 30/25 °C) with a photoperiod of 14 h. Aggressiveness, recorded as area under the disease progress curve (AUDPC), of South American isolates was higher than for European isolates at 15 °C, 20 °C and 25 °C, and for sporulation in vivo in all temperatures. In general, aggressiveness components were most influenced by temperature. Therefore, multivariate analysis was performed with aggressiveness component data at 30 °C, which expressed the highest number of variables with significant differences between isolate origins. According to their aggressiveness, European and South American isolates can be grouped separately, demonstrating that South American isolates are better adapted to higher temperatures and display a higher level of aggressiveness under similar conditions than European isolates from a cool climate. It is concluded that plasticity of temperature adaptation in E. turcicum populations is relatively large and allowed E. turcicum to follow the recent expansion of maize cultivation into cool climate zones in Europe. However, our data suggest that adaptation to higher temperature is likely to increase aggressiveness of NCLB on maize in cooler climate zones when experiencing further climate warming. This plasticity in adaptation to environmental conditions of E. turcicum may also hamper the success of breeding programs as it may decrease the durability of resistance.
Keywords: Aggressiveness; Climate warming; Leaf disease; Setosphaeria turcica